Case Report: Transformation From Non-Small Cell Lung Cancer to Small Cell Lung Cancer During Anti-PD-1 Therapy: A Report of Two Cases - Shen, Qian; Qu, Jingjing; Sheng, Lingyan; Gao, Qiqi; Zhou, Jianying (Frontiers in Oncology, 2021)
Background: Histologic transformation to small cell lung cancer (SCLC) is a common phenomenon in patients with epidermal growth factor receptor (EGFR) mutations receiving EGFR-tyrosine kinase inhibitors (EGFR-TKIs). However, reports on programmed cell death-1 (PD-1) inhibitors are rare. Herein, we report two cases of lung squamous carcinomas that were transformed to SCLC during anti-PD-1 therapy with detailed histological examination of the pre-and post-transformation tissues, which is absent in prior reports. Case presentation: Case 1: A 69-year-old man was diagnosed with stage IVa lung squamous cell carcinoma. He had a programmed cell death-ligand 1 tumor proportion score ≥50%. He achieved partial response after four cycles of sintilimab as first-line treatment. However, sintilimab was discontinued because of a severe decrease in hemoglobin levels and platelet counts. Subsequently, pleural effusion favored disease progression. Finally, bone marrow puncture and biopsy showed a transformation to SCLC. Case 2: A 71-year-old man was diagnosed with stage IIIa lung squamous cell carcinoma. He received neoadjuvant chemotherapy, underwent radical surgery, and adjuvant chemotherapy. Five months later, he presented with tumor recurrence. He was treated with nivolumab, and disease progression was observed after four cycles. However, a subsequent computed tomography-guided biopsy showed SCLC. Conclusion: Phenotypic transformation to SCLC is a potential mechanism of resistance to immunotherapy in lung squamous cell carcinomas. Disease progression should prompt re-biopsy to diagnose the change in histology and requirement for treatment change.